Acute effects of radiofrequency electromagnetic field emitted by mobile phone on brain function. Issue 5 (20th April 2017) - Zhang, Jun; Sumich, Alexander; Wang, Grace Y.
Abstract : Due to its attributes, characteristics, and technological resources, the mobile phone (MP) has become one of the most commonly used communication devices. Historically, ample evidence has ruled out the substantial short‐term impact of radiofrequency electromagnetic field (RF‐EMF) emitted by MP on human cognitive performance. However, more recent evidence suggests potential harmful effects associated with MP EMF exposure. The aim of this review is to readdress the question of whether the effect of MP EMF exposure on brain function should be reopened. We strengthen our argument focusing on recent neuroimaging and electroencephalography studies, in order to present a more specific analysis of effects of MP EMF exposure on neurocognitive function. Several studies indicate an increase in cortical excitability and/or efficiency with EMF exposure, which appears to be more prominent in fronto‐temporal regions and has been associated with faster reaction time. Cortical excitability might also underpin disruption to sleep. However, several inconsistent findings exist, and conclusions regarding adverse effects of EMF exposure are currently limited. It also should be noted that the crucial scientific question of the effect of longer‐term MP EMF exposure on brain function remains unanswered and essentially unaddressed. Bioelectromagnetics. 38:329–338, 2017. © 2017 Wiley Periodicals, Inc.